Exploring the impacts of implicit context association and arithmetic booster in impulsivity reduction - Hwang, Minho; Kim, Sung-Phil; Chung, Dongil (Frontiers in Psychiatry, 2022)
People have a higher preference for immediate over delayed rewards, and it is suggested that such an impulsive tendency is governed by one’s ability to simulate future rewards. Consistent with this view, recent studies have shown that enforcing individuals to focus on episodic future thoughts reduces their impulsivity. Inspired by these reports, we hypothesized that administration of a simple cognitive task linked to future thinking might effectively modulate individuals’ delay discounting. Specifically, we used one associative memory task and one working memory task that each of which was administered to intervene acquired amount of information and individuals’ ability to construct a coherent future event, respectively. To measure whether each type of cognitive task reduces individuals’ impulsivity, a classic intertemporal choice task was used to quantify individuals’ baseline and post-intervention impulsivity. Across two experiments and data from 216 healthy young adult participants, we observed that the impacts of intervention tasks were inconsistent. Still, we observed a significant task repetition effect, such that participants showed more patient choices at the second impulsivity assessment. In conclusion, there was no clear evidence supporting that our suggested intervention tasks reduce individuals’ impulsivity, while the current results call attention to the importance of taking into account task repetition effects in studying the impacts of cognitive training and intervention.